Analysis of the thermal behavior of a fixed bed reactor during the pyrolysis process: Original scientific paper - Đurđević, Milica; Papuga, Saša; Kolundžija, Aleksandra (HEMIJSKA INDUSTRIJA (Chemical Industry), 2023)
Pyrolysis is a thermochemical process of degradation of organic compounds where the reaction takes place in an inert atmosphere. The process scale varies between industrial, semi-industrial or laboratory. During the pyrolysis process temperature has to be controlled, but, most of pyrolysis studies do not clearly state where the temperature is measured and weather the temperature field is uniform. In this paper thermal behavior of a laboratory scale fixed-bed reactor and energy consumption during pyrolysis processes were analyzed. Three different samples were used: mixture of plastic waste (sample 1), biomass (sample 2) and mixture of plastic waste and biomass (sample 3). The analysis of the thermal behavior of the reactor indicates that with careful regulation or temperature control of the process, one can obtain diagrams that can be used for the purpose of recording thermally intensive processes, similar to more complex thermogravimetric (TG) and derivative thermogravimetric (DTG) analyses. It has been shown that it is possible to change the heating rate and the overall energy efficiency of the process by simply choosing the appropriate raw material mixture. osing the appropriate raw material mixture.